One-year measurements of chloroethenes in tree cores and groundwater at the SAP Mimoň Site, Northern Bohemia - Wittlingerova, Z; Machackova, J; Petruzelkova, A; Trapp, S; Vlk, K; Zima, J (Environmental science and pollution research international, 2013)
Chlorinated ethenes (CE) are among the most frequent contaminants of soil and groundwater in the Czech Republic. Because conventional methods of subsurface contamination investigation are costly and technically complicated, attention is directed on alternative and innovative field sampling methods. One promising method is sampling of tree cores (plugs of woody tissue extracted from a host tree). Volatile organic compounds can enter into the trunks and other tissues of trees through their root systems. An analysis of the tree core can thus serve as an indicator of the subsurface contamination. Four areas of interest were chosen at the experimental site with CE groundwater contamination and observed fluctuations in groundwater concentrations. CE concentrations in groundwater and tree cores were observed for a 1-year period. The aim was to determine how the CE concentrations in obtained tree core samples correlate with the level of contamination of groundwater. Other factors which can affect the transfer of contaminants from groundwater to wood were also monitored and evaluated (e.g., tree species and age, level of groundwater table, river flow in the nearby Ploučnice River, seasonal effects, and the effect of the remediation technology operation). Factors that may affect the concentration of CE in wood were identified. The groundwater table level, tree species, and the intensity of transpiration appeared to be the main factors within the framework of the experiment. Obtained values documented that the results of tree core analyses can be used to indicate the presence of CE in the subsurface. The results may also be helpful to identify the best sampling period for tree coring and to learn about the time it takes until tree core concentrations react to changes in groundwater conditions. Interval sampling of tree cores revealed possible preservation of the contaminant in the wood of trees.
Keywords: látky znečišťující životní prostředí; stromy; Environmental Monitoring; Hydrocarbons, Chlorinated; monitorování životního prostředí; podzemní voda; Environmental Pollutants; Groundwater; Trees; Česká republika; chlorované uhlovodíky; Czech Republic